ChemInform Abstract: Iron‐Catalyzed Chemoselective Azidation of Benzylic Silyl Ethers. Issue 20 (25th April 2013) - Sawama, Yoshinari; Nagata, Saori; Yabe, Yuki; Morita, Kosuke; Monguchi, Yasunari; Sajiki, Hironao
Abstract Secondary and tertiary benzyl silyl ethers are transformed to the azido products selectively in the presence of primary benzyl silyl ethers [e.g. (IX)], alkyl chlorides [e.g. (IIId)], and α, β‐unsaturated esters [e.g. (XI)] under mild conditions and in short reaction times.